Math is easy 1.0 / Nadiah Mohamed ... [et al.] - Mohamed, Nadiah; Yaacob, Nurul Aityqah; Mahayadin, Mahfuzah; Mohd Ruslan, Siti Zaharah; Ismail, Norul Fadhilah; Othman, Norlida; Andu, Yusrina; Najib Harif, Muhammad (Universiti Teknologi MARA, Negeri Sembilan, 2023)
On January 13, 2023, the College of Computing, Informatics, and Media Studies UiTM Negeri Sembilan Kampus Kuala Pilah hosted Math is Easy 1.0. A total of 150 students were involved, consisting of Pre-Science, STEM-C, and Pre-Academy of Islamic Contemporary Studies. All of the lecturers who teach the pre-students in their own subjects ran the session. Students in this program are taught how to answer the correct method of a final exam question. They are also given tips for full marks in each question answered. Positive feedback was also provided by the students who participated throughout the program.